The moderating effects of personal characteristics and motivational factors on the propensity to use sports events tourism websites - Radzliyana, Radzuwan (2016)
Despite plenty of research related to the Internet has been conducted throughout the world, there remains a shortage of knowledge pertaining to personal characteristics and motivational factors as the moderating effects on the propensity to use sports events tourism websites. Thus, this study was conducted to investigate roles of moderating effects on the relationship between customer-perceived value and the propensity to use sports events tourism websites. This study has utilized the Sport Website Acceptance Model (SWAM) and the Uses and Gratification Theory (UGT) as the research background theories. Therefore, four components of customer-perceived value which extracted from the factor analysis were accessibility, flexibility, interactivity and reliability, acted as independent variable. While, motivation in terms of informativeness gratification and entertainment gratification acted as the moderating variables. This study has utilized a self-administered questionnaire adapted from a standardized questionnaire based on the literature review. The sample of the study comprised of 530 sports tourists’ (315 males and 215 females) who participated in three major sporting events conducted in Malaysia in 2013. The probability sampling technique was applied to select the respondent. The results of Pearson correlation analyses showed that there was a significant relationship between customer-perceived value and the propensity to use the websites. The stepwise multiple regression analyses showed that amongst four moderating variables of personal characteristics (age, gender, education, and income) except income did not moderate the relationship between customer-perceived value and the propensity to use the websites. The result of the study also indicates that 14.8 percent of the total variance of the propensity to use the websites was explained by customer-perceived value, entertainment gratification, informativeness gratification, the combination of customer-perceived value and entertainment gratification as well as the combination of customer-perceived value and informativeness gratification. The research findings would be practical and useful for sports tourism organizations in providing distinctive sports tourism websites on how to market their products and/or services effectively